Recurrent Ischemic Stroke Characteristics and Assessment of Sufficiency of Secondary Stroke Prevention - KOCAMAN, Gulsen; DURUYEN, Humeyra; Kocer, Abdulkadir; Asil, TALİP; ASİL, TALIP (My University, 2015)
Introduction: Disabilities due to stroke lead to a serious individual and socioeconomic burden. In this presented hospital-based study, we aimed to evaluate recurrent ischemic stroke (RIS) characteristics and the sufficiency of secondary prevention regarding the most common modifiable risk factors. Methods: The records of patients with a diagnosis of ischemic stroke between November 2009 and November 2011 in our unit were retrospectively investigated. Results: Ninety-one (18%) out of 500 patients with ischemic stroke had RIS. Hypertension, diabetes mellitus, ischemic heart disease, hyperlipidemia, atrial fibrillation, and smoking were found in 88%, 43%, 36%, 30%, 11%, and 14% of the patients, respectively. Thirty-eight percent of the patients had more than two risk factors. While 14% of the hypertensive patients did not use antihypertensive medications, antihypertensive treatment was insufficient in 39% of those who already used antihypertensive medications. Twenty-three percent of the patients received no prophylactic agents. Sixty percent of the patients with a history of atrial fibrillation were on oral anticoagulant therapy (warfarin), and the international normalized ratio was <2.0 in 73% of them. Of the diabetic patients, 87% had an HgbA1C level above 6%. The LDL level was higher than 100 mg/dL in 72% of the patients. Conclusion: The incidence of RIS and risk factors in our retrospective study was compatible with the results of those in literature. Secondary prophylactic treatment and modification of risk factors in the stroke patients were not satisfactory. The improvement of the patients' adherence to treatment is also very important in addition to the optimal treatment and follow-up strategy for decreasing the incidence of RIS. A multidisciplinary outpatient model of stroke care may be beneficial for decreasing the incidence of RIS.
Keywords: Recurrent stroke; Risk factors; Secondary prevention